2018
DOI: 10.1073/pnas.1721267115
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected metabolic disorders induced by endocrine disruptors in Xenopus tropicalis provide new lead for understanding amphibian decline

Abstract: Despite numerous studies suggesting that amphibians are highly sensitive to endocrine disruptors (EDs), both their role in the decline of populations and the underlying mechanisms remain unclear. This study showed that frogs exposed throughout their life cycle to ED concentrations low enough to be considered safe for drinking water, developed a prediabetes phenotype and, more commonly, a metabolic syndrome. Female exposed from tadpole stage to benzo()pyrene or triclosan at concentrations of 50 ng⋅L displayed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 85 publications
(81 reference statements)
4
29
0
1
Order By: Relevance
“…The control frogs were exposed to dimethyl sulfoxide (DMSO, vehicle) at a concentration of 4/1000 (v:v). As described in Regnault et al (2018), pollutant concentrations in the medium were continually monitored using GC-MS/MS, and confirmed that the average weekly BaP/TCS concentrations were both equal to 50 ng.L -1 . These concentrations match the BaP and TCS concentrations found in polluted ponds (Trapido and Veldre, 1996;Lindström et al, 2002;Blair et al, 2013;Olivares-Rubio et al, 2015).…”
Section: Exposuresupporting
confidence: 59%
See 4 more Smart Citations
“…The control frogs were exposed to dimethyl sulfoxide (DMSO, vehicle) at a concentration of 4/1000 (v:v). As described in Regnault et al (2018), pollutant concentrations in the medium were continually monitored using GC-MS/MS, and confirmed that the average weekly BaP/TCS concentrations were both equal to 50 ng.L -1 . These concentrations match the BaP and TCS concentrations found in polluted ponds (Trapido and Veldre, 1996;Lindström et al, 2002;Blair et al, 2013;Olivares-Rubio et al, 2015).…”
Section: Exposuresupporting
confidence: 59%
“…The hepatosomatic index (HSI) was calculated by dividing the weight of the liver by the body weight and hepatoxicity was evaluated by measuring alanine aminotransferase activity in serum as previously described in Regnault et al (2018).…”
Section: Hepatosomatic Index and Hepatotoxicitymentioning
confidence: 99%
See 3 more Smart Citations